Selection attributes of Korean restaurant based on customer satisfaction and loyalty/ Nurul Shahiera Mohd Raihan ... [et al.] - Mohd Raihan, Nurul Shahiera; Osman, Suriati; Abdul Rahman, Faradewi Bee; Ismail, Faridah Hanim; Isa, Nina Farisha (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The restaurant industry is one of the most important sectors in Malaysia and contribute significantly to the economic growth. The positive perceptions of Korean food among Malaysian have created opportunities for the Korean restaurant owners to expand their outlet in the Malaysian market. The study aimed to examine relationships between restaurant selections attributes for a Korean restaurant and customer loyalty as well as to examine customer satisfaction as a mediating factor. The questionnaires were distributed to customers in Kuala Lumpur using a convenient sampling approach via online method. Total of 399 feedback was gathered and analyse using SPSS version 26. The results show that there is strong positive relationship between restaurant selection attributes for a Korean restaurant, customer satisfaction and customer loyalty. However, standard hygiene has a negative direct relationship with customer loyalty but contribute positively to the customer satisfaction. The results also reveal that, customer satisfaction mediate positively with restaurant selection attributes and customer loyalty. This study has significant contribution to academician and practitioners in the area of consumer behaviour.